Demonstration of the ascending aorta in infective endocarditis by intravenous digital subtraction angiography. Issue 3 (September 1988) - Hunter, G J; Thomas, H; Treasure, T; Sturridge, M F; Swanton, R H
Abstract : Four patients with infective endocarditis were examined by digital subtraction angiography immediately before operation. In three a root abscess was suspected and the remaining patient was believed to have a false aneurysm at an infected aortic cannulation site. In all the cases digital subtraction angiography showed the structure in several projections and confirmed the presence of a cavity. Subsequent operation confirmed the site and nature of the lesions.